Employment in SMEs in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
Of the two billion people expected to join the world population by 2050, over half are expected to come from sub-Saharan Africa. With an employed, educated and skilled population, the region could experience rapid and sustained economic growth, but this can only be achieved if countries in sub-Saharan Africa succeed in offering sufficient economic opportunities that can absorb their burgeoning workforce. As such, this research work focuses on the role of Small and Medium Enterprises (SMEs) in addressing sub-Saharan Africa’s significant employment needs and the issues surrounding the formalization of these jobs. Chapter 1 looks at quantitative job creation to determine whether African SMEs have a greater potential for job creation than large firms do. Using data from the World Bank's Enterprise Surveys, we test Gibrat's law, which states that size does not influence firm growth. We find that this law does not hold in Sub-Saharan Africa, i.e. small companies create more jobs than large companies. We show that the usual explanations (diminishing returns, the learning effect, optimal size) do not explain this rejection. We present a new hypothesis based on access to capital and argue that small firms have a lower capital-to-labor ratio because they overuse labor input due to financial constraints.Chapter 2 introduces the existing literature on informality in order to better understand the issues surrounding this phenomenon and the determinants that give rise to its widespread presence across sub-Saharan Africa. Chapter 3 explores employees' willingness to join a health insurance system by analyzing their individual preferences. We show that despite the preference for the present and the low aversion to risk that would predispose an individual not to obtain health insurance, employees expressed a significant increase in their willingness to enroll in a health insurance system after receiving information on the role and benefits thereof.Chapter 4 documents
Keywords: African Research